Análise nacional do ciclo da política de educação, ciência e tecnologia nos Institutos Federais - IFs: a carência epistêmica e a produção do homo enterprise no contexto da prática e na atuação política - Sobrinho, Sidinei Cruz (2023)
The general objective of the thesis is to analyze the Professional and Technological Education [EPT] policy cycle in Federal Institutes [IFs], at a national level, formally established by Law No. 11,892/2008. It seeks, among other specific objectives, to identify the main characteristics of the context of political practice and action, as well as the main effects, directions and strategies of this policy. It takes as a historical cut-off the years 2008 to 2022. Its main theoretical field is educational policies, in interdisciplinarity with the philosophical, legal, educational and political science fields. The research is classified as: 1 - Nature/purpose: Basic; 2 - Policy Cycle Approach [ACP] Quanti-qualitative. 3 - Objectives: Explanatory; 4 - Procedures: bibliographic, documentary, Legal-philosophical Hermeneutics, Tabulation of quantitative data and Organization of qualitative categories, Interdisciplinary. The Materiality and empirical nature of the research are based on: 1) Bibliographic and Documentary Sources; 2) Legislative Sources, mainly formal state legislative sources; 3) Sources of Quantitative Indicators, 4) Sources of the researcher's Experiences in the Context of Practice. The ACP method, by Ball and collaborators, was mainly used. The Educational Policy Epistemology Approach (EEPE) under analysis was supported by the following dimensions: 1. "Epistemological perspective" (theoretical): theory of policy enactment and theory of global educational policy, based on Ball, as well as critical/neo-Marxist theory, based on Laval and Dardot; et al., that is, on a Combined Theorization basis; 2. "Epistemological positioning": analytical critique in relation to the educational policy of IFs, and in relation to the neoliberal epistemological positioning. 3. "Epistemethodological approach": interdisciplinarity based on ACP, criticism of neoliberalism and its influence on the social function of Education, in the Democratic Rule of Law. As well as from the Hermeneutic-legal perspective in relation to the analysis of the main normative text of the IFs Educational Policy. The study seeks to provoke (im)pertinent reflections on analysis and possibilities for educational policy strategies.It aims to answer the question whether, since the beginning of the EPT Policy Cycle in FIs, enactment in the context of practice has come closer to or distanced itself from the conceptions, priorities, objectives and purposes for which it was established as defended in the Context of Influence and in the Text Production Context, and has led to significant effects of structural change to guarantee the rights to Education and Work. The research concludes by highlighting the progressive separation between the policy proposed in the contexts of influence and production of the text and the policy actually exercised/acted in the contexts of practice and effects. This reality deepens the desymbolization of education and political action that is increasingly distant from the social function understood as an instrument of social justice. Positive results are presented that significantly affect the lives of some individuals, but, unfortunately, they are still actions of a palliative nature, without causing structural changes. In this area, the research also presents some viable policy strategies and points out ways to deepen the perspective of an effectively contextualized policy analysis that is not limited to a merely economic and quantitative orientation of meeting efficiency criteria. In this sense, it points out that, in addition to these, it also considers local and regional specificities and a cultural socioeconomic perspective as an educational policy at the national level.